Financing road infrastructure in China and India: current trends and future options - Antonio Postigo (Journal of Asian Public Policy, 2008)
Road infrastructure has been a key input in the economic growth and poverty reduction strategies of China and India. The two countries have used very different instruments for road financing with China mobilizing substantial resources through directed credit by state-owned banks and India heavily relying on international institutions and fuel taxes. However, current modalities of road financing will be insufficient to meet future investment needs requiring both countries explore new mechanisms to attract private capital and expand the fiscal space of central and subnational governments. Different instruments of resource mobilization and intermediation are assessed and compared extracting lessons that could be valuable to many developing countries. Facilitating the participation of the private sector in road development would require inter alia strengthening regulatory frameworks and deepening and broadening domestic financial markets. But given the strong public good characteristics of large segments of the road networks in China and India most of the funding for road construction and maintenance would need to come from the establishment of efficient and sustainable systems of earmarked road-related charges, including a fuel tax in China.
Keywords: 320